Formulation of NSF H2 food-grade grease from vegetable-base oils - Mohd Najib, Razali; Nur Syahirah, Juhari; Nur Kholis, Zulkifli; Najmuddin, Mohd Ramli; Mohd Khairul Nizam, Mohd Zuhan (Springer, 2024)
Vegetable oil is a potentially non-toxic, safe source, sustainable and cost-effective of obtaining environmentally friendly lubricants. This study aims to formulate NSF H2 food-grade greases from three types of vegetable base-oils (VBO): palm oil (fresh and used), coconut oil (fresh and used), and castor oil. Lithium-12-hydrostearic acid, azelaic acid, and butylated hydroxytoluene were used as a thickening agent, complexing agent and an additive, respectively. Similar ratios of base oils, thickener, and additive were used in all five grease formulations and were tested based on ASTM. The physical properties of the oils were characterised for water content, viscosity, flashpoint, and thermal stability. The chemical composition and functional groups of the oils was evaluated via GC–MS and CHNOS elemental analysis, and FTIR. The formulated greases were analysed for consistency, dropping point, stability, oil bleeding, and thermal analysis. The analysis shows the grease made of vegetable base-oils (VBO) exhibit high dropping points exceeding 200 °C and NLGI 2 for fresh palm oil, used palm oil, and castor oil-based greases, and NLGI 1 and 3 for fresh and used coconut oil-based grease, respectively. Castor oil shows high bleeding with 22.88%, the greases made of fresh palm oil and fresh coconut oil have moderate oil bleeding of 1.20–7.55%.